(untitled) (Al-Academy, 2023)
Research on sustainable design in Iraqi craft industries and ways to develop them is essential to preserving the cultural heritage and authenticity of these industries while promoting environmentally sustainable practices. Lack of access to modern technologies, knowledge and resources may hinder the growth of these industries and their ability to compete in the global market. The research problem revolves around finding ways to develop sustainable design in the Iraqi craft industries. The expected outcomes of this research include a clear definition of sustainable design, understanding the history of sustainable design in the craft industry, identifying different types of craft industries in Iraq, exploring the basic concepts of sustainable design, evaluating the effectiveness of processing reeds and palm fronds, and identifying natural materials that can be used in craft industrial products in Iraq. Finally, this research can contribute to the development of sustainable and competitive craft industries in Iraq that comply with sustainable design principles, preserve the country’s cultural heritage, and promote sustainable development.